(untitled) (Brazilian Journal of Oceanography, 2011)
Previous studies examining the dynamics of succession on artificial reefs have predominantly focussed on fish communities and largely ignored the role of fouling assemblages in explaining the patterns of community structure associated with artificial reefs. The objective of this study was to record the development of epibiotic assemblages on three "design specific" (Reef Ball®) estuarine artificial reefs systems located in Lake Macquarie, Botany Bay and St Georges Basin in New South Wales, Australia. Recruitment to the artificial reefs was relatively rapid with the majority of taxa identified over the two-year study period observed within the first year post-deployment. The artificial reefs in Lake Macquarie and St Georges Basin were characterised by low diversity with four and nine taxa recorded respectively in contrast to the sixteen taxa observed on the Botany Bay reefs. Results indicated no significant differences in percentage cover of taxa among reefs in either St Georges Basin or Lake Macquarie. In contrast, comparisons between individual Botany Bay reefs identified significant differences in the percentage cover of species between artificial reefs. Analysis of assemblage structure with reef age indicated discrete patterns among estuaries with an overall reduction in the percentage cover of filamentous turfing algae (FTA) identified for all reef systems with an increase in reef age. Variations in environmental and physical conditions (turbidity, water flow, wave action and proximity to naturally occurring reef) may have contributed to the observed differences in fouling assemblages between estuaries and between artificial reefs within Botany Bay.